Political Consultation and Public Opinion Polls - طوينة علي حسين (ALBAHITH ALALAMI, 2016)
Increasingly important public opinion polls steadily .... especially in electoral campaigns, sheds searchlight on the side of the US elections, in different time periods, and cited the words of experts and people involved in it, and reviews Find great development that took place in the polls and what could happen to this work It is important in the future. Display search for certain types of polls, dividing them on as stated by the experts in the United States... This division shows that the surveys of the most political processes and accuracy of information, and that their Money being made and companies specialized in the administration of this type of measuring public opinion ..... what is returned decision-making, for example, in conjunction elections or prepare a plan to lead the country not easy or hasty, we have to resort to the companies, which are major companies usually measure the truth of what he wants Opinion year, but such a measure is not always guaranteed ..... Valnachb example, his decision may alter the length of the other, or may idly for real in his opinion, for various reasons. And that this volatility in the views, is a problem for those who want to reach a scientific accuracy in measuring public opinion ...... Scientific surveys in 1960 have emerged Kachtsas seriously consultant, the benefit of candidates at all levels. That contemporary surveys are based on the principle of the random sample, the random sample can give a good opportunity for everyone, from the group, to be represented equally in (.....) In order to achieve a margin of error, we should increase the size of the sample, but when we increase The sample size will increase the cost. If we increased our sample size and made it is made up of two thousand people, we will have increased our campaign costs dramatically reduced the margin of error by 1%.